Effective CKD care in European countries: challenges and opportunities for health policy - Bello, Aminu K.; Levin, Adeera; Manns, Braden J.; Feehally, John; Drueke, Tilman; Faruque, Labib; Hemmelgarn, Brenda R.; Kernahan, Charles; Mann, Johannes; Klarenbach, Scott; Remuzzi, Giuseppe; Tonelli, Marcello (American Journal of Kidney Diseases, 2015)
Chronic kidney disease (CKD) is an important global public health problem that is associated with adverse health outcomes and high health care costs. Effective and cost-effective treatments are available for slowing the progression of CKD and preventing its complications, including cardiovascular disease. Although wealthy nations have highly structured schemes in place to support the care of people with kidney failure, less consideration has been given to health systems and policy for the much larger population of people with non-dialysis-dependent CKD. Further, how to integrate such strategies with national and international initiatives for control of other chronic noncommunicable diseases (NCDs) merits attention. We synthesized the various approaches to CKD control across 17 European countries and present our findings according to the key domains suggested by the World Health Organization framework for NCD control. This report identifies opportunities to strengthen CKD-relevant health systems and explores potential mechanisms to capitalize on these opportunities. Across the 17 countries studied, we found a number of common barriers to the care of people with non-dialysis-dependent CKD: limited work force capacity, the nearly complete absence of mechanisms for disease surveillance, lack of a coordinated CKD care strategy, poor integration of CKD care with other NCD control initiatives, and low awareness of the significance of CKD. These common challenges faced by diverse health systems reflect the need for international cooperation to strengthen health systems and policies for CKD care.
EVALuna2:3882